Literasi Bahaya Penggunaan Radiasi pada Siswa Madrasah Tsanawiyah Miftahul Ulum Melirang Bungah Gresik - Nastiti Faradilla Ramadhani; Deny Saputra; Aga Satria Nurrachman (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
Radiation is any kind of energy transmitted without an intermediate medium. Radiant energy is generally wave-shaped, most commonly sinusoidal. There are two types of radiation: ionizing radiation and non-ionizing radiation. Ionizing radiation is radiation that causes the process of ejecting electrons from atoms to form ion pairs. Attention should be paid to ionizing radiation, particularly its sources, types, properties, effects, and methods of avoidance. Ionizing radiation is well known, for example radiation from X-rays. Non-ionizing radiation can occur in equipment and mobile phones. Miftaful Ulm Merilan Madrasah Tsanawaya School is in Merilan Village, Bunga District, Eastern Gresik Regency. The location of this school is far from the city center. Student health contributes to the smooth running of the educational process. There is a lack of knowledge and awareness among students and residents in Bunga district that radiation hazards affect their quality of life. A technical implementation of this training will help you address the material. Students were assessed using pretests and posttests. The mean score before the pretest was 32.7, and after listening to the material and after the posttest was 80.